Safety assessment of poly-ε-caprolactone in the treatment of primary spontaneous pneumothorax - How, Cheng-Hung; Chen, Pei-Hsing; Chen, Yu-Ching; Lin, Yong-Chong; Chen, Ke-Cheng; Chen, Jin-Shing; Young, Tai-Horng (Frontiers in Surgery, 2024)
Background/Purpose: Biomaterial-based implants are gaining traction as an option for pleurodesis treatment, yet the search for the best biomaterial or the most suitable shape to handle spontaneous pneumothorax continues. This forward-looking research assessed the use of a poly-ε-caprolactone membrane for its safety when applied as a sclerosant in pleurodesis procedures in human patients. Methods: From July 2017 to February 2018, we conducted a Phase I trial in which 10 patients with primary spontaneous pneumothorax were treated using video-assisted thoracoscopic surgery with a poly-ε-caprolactone membrane. These procedures encompassed bleb resection and mechanical pleurodesis through parietal pleura scrubbing. After resection, a 150 × 150 mm poly-ε-caprolactone membrane was applied to the apex. The primary outcome measures were the adverse events and laboratory outcomes. Results: After surgery, we observed no cardiopulmonary-related adverse events or indications of systemic inflammation. Furthermore, no episodes of hypothermia or hyperthermia occurred. Chest radiographs showed no evident pneumonitis or effusion associated with tissue reactions. The average follow-up duration was 31.7 ± 17.7 months, during which two patients exhibited This is a provisional file, not the final typeset article recurrence. Conclusion: This study is the first to show the biocompatibility of poly-ε-caprolactone in humans, suggesting its potential as a treatment option for patients with primary spontaneous pneumothorax. Despite the relatively small number of patients, we maintain confidence in the reliability and safety profile of the PCL membrane, bolstered by its previously established efficacy in applications involving other organs. Phase II and phase III clinical studies are needed to support these observations.